Case report: Treatment of joint supplement toxicity resulting in acidemia, hyperglycemia, electrolyte derangements, and multiple organ dysfunction - Bunnell, Nicole M.; Weatherton, Linda (Frontiers in Veterinary Science, 2023)
Objective: This case report describes a successful outcome in the treatment of a patient with joint supplement toxicity which resulted in seizures, severe acidemia, hyperglycemia, hypernatremia, and multiple organ dysfunction. Previous case reports have been published but this patient presented with different clinical signs and had additional biochemical abnormalities. Treatment modalities varied in this case report and the patient was discharged sooner compared to previous reports. Case Summary: A 9-year-old spayed female Maltese mix presented to a specialty hospital for joint supplement toxicity. Presenting clinical signs were vomiting and seizures. Primary biochemical abnormalities consisted of hypernatremia, hyperglycemia, acidemia, azotemia and elevated liver enzymes. Treatment involved lowering the sodium quickly given the neurologic signs on presentation. Other treatment modalities consisted of sodium bicarbonate, insulin, and liver protectants. The patient responded quickly and was discharged after three days in the hospital. New or Unique Information Provided: This case report is different in that the patient was having seizures and was also hyperglycemic, in addition to the expected abnormalities of hypernatremia, acidemia and multiple organ dysfunction. It also differs in that the treatment of hypernatremia was managed as an acute process compared to prior reports. This case report describes differing clinical signs, biochemical abnormalities and treatment modalities which may have led discharge from hospital in a shorter time.